2020
DOI: 10.1038/s41598-020-62679-4
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of tidally generated internal waves in the north-central Bay of Bengal

Abstract: Flow of barotropic tidal currents over topographic features, such as continental slopes and submarine ridges, generates internal gravity waves at tidal periods known as internal tides. Amplitude of these waves are generally large near the generation regions. Analysis of Sea Surface Height (SSH) data, derived from satellite altimeter revealed the amplification of internal tides in the semidiurnal period in the north-central Bay of Bengal (BoB) (around 89  E, 16  N), which is about 450 km away from their gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Model‐simulated currents and temperature were validated with velocity measurements obtained from ADCP moorings along the western BoB and open ocean moorings in the BoB (Francis et al., 2020; Jithin et al., 2017). Simulations from this model were also used to study boundary currents (Francis et al., 2020), internal tides (Jithin & Francis, 2020; Jithin, Francis, et al., 2020, Jithin, Subeesh, et al., 2020), and coastal‐trapped waves along the boundaries of the BoB (Anup et al., 2021). Therefore, model validation in this paper is restricted to the comparison of observed and simulated ITE in the northern BoB using observations from RAMA moorings.…”
Section: Methodsmentioning
confidence: 99%
“…Model‐simulated currents and temperature were validated with velocity measurements obtained from ADCP moorings along the western BoB and open ocean moorings in the BoB (Francis et al., 2020; Jithin et al., 2017). Simulations from this model were also used to study boundary currents (Francis et al., 2020), internal tides (Jithin & Francis, 2020; Jithin, Francis, et al., 2020, Jithin, Subeesh, et al., 2020), and coastal‐trapped waves along the boundaries of the BoB (Anup et al., 2021). Therefore, model validation in this paper is restricted to the comparison of observed and simulated ITE in the northern BoB using observations from RAMA moorings.…”
Section: Methodsmentioning
confidence: 99%
“…2c). Recently, Jithin et al 24,39 have reported that the internal tides, which radiate westward from the AN Ridge, propagate over large distances (1,000-1,400 km) across the BoB. They further showed that a part of these internal tides that shoal onto the continental margins of the east coast of India get further transmitted on to the inner shelf and eventually dissipate there.…”
Section: Resultsmentioning
confidence: 98%
“…Angle brackets ( ) indicate average over a tidal period 44 . Detailed discussion on the internal tide energy budget and its estimation can be found in Jithin et al 24 , 39 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standing internal tides with seasonal shifts have been reported in other regions e.g., the Hawaiian Ridge (Rainville et al, 2010), the South China Sea (Ray & Zaron, 2011), and the Bay of Bengal (Jithin et al, 2020). Zaron (2019) reported the global distribution of seasonally modulated 2 E M baroclinic sea surface height variance (…”
Section: 1029/2021jc017570mentioning
confidence: 89%